Electroluminescence spectra of an STM-tip-induced quantum dot - Croitoru, Mihail D.; Gladilin, Vladimir N.; Fomin, Vladimir M.; Devreese, Jozef T.; Kemerink, Martijn; Koenraad, Paulus M.; Sauthoff, Katharina; Wolter, Joachim H. (Physica. E, Low-dimensional systems & nanostructures, 2004)
We analyze the electroluminescence spectrum of an STM-tip-induced quantum dot in a GaAs surface layer. A flexible model has been developed, that combines analytical and numerical methods and describes the key features of many-particle states in the STM-tip-induced quantum dot. The dot is characterized by its depth and lateral width, which are experimentally controlled by the bias and the tunneling current. We find, in agreement with experiment, that increasing voltage on the STM-tip results in a red shift of the electroluminescence peaks, while the peak positions as a function of the electron tunneling current through the STM-tip reveal a blue shift.